Using clinical variables to evaluate treatment effectiveness in programmes for sexual offenders - Jung, Sandy; Gulayets, Michael (My University, 2011)
Typically, sex offender programmes are evaluated using recidivism, a distal outcome measure. This paper proposes that sex offender programmes also incorporate proximal variables to evaluate treatment effectiveness. Proximal variables assess within treatment changes immediately following the intervention. To demonstrate this approach, the effectiveness of a sex offender treatment programme is evaluated using proximal variables, specifically locus of control, empathy, cognitive distortions and acceptance of responsibility. We provide the findings of this evaluation and discuss the implications of this approach. In particular, we conclude with the importance of identifying relevant treatment targets and selecting suitable proximal measures of those targets in evaluating treatment effectiveness.
Keywords: change; clinical variables; effectiveness; proximal; sex offenders; treatment